Analyse des représentations du discours autre en discours direct et discours indirect lors des discussions à visée philosophique - Philippe Roiné (Nantes Université, 2016)
The objective of our study was to characterize the processes of conceptualization within the discussions with philosophical aim in primary education. In this end, we have integrated the concept of "dialogism" (Bakhtin, 1978, 1984) now widely used in the discourse analysis. We examined different linguistic forms based on Bakthin's and Auhtier-Revuz's studies on discourse representation. By analyzing five discussions, we noted the origins of the "other speeches".